2007
DOI: 10.2340/16501977-0039
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial to evaluate the ActiGait implanted drop-foot stimulator in established hemiplegia

Abstract: Objective: To evaluate a selective implantable drop foot stimulator (ActiGait) in terms of effect on walking and safety. Design: A phase II trial in which a consecutive sample of participants acted as their own controls. Subjects: People who had suffered a stroke at least 6 months prior to recruitment and had a drop-foot that affected walking were recruited from 3 rehabilitation centres in Denmark. Methods: Stimulators were implanted into all participants. Outcome measures were range of ankle dorsiflexion with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 18 publications
3
85
0
Order By: Relevance
“…O'Halloran et al made similar conclusions about generating pure dorsiflexion without inversion or eversion through balanced activation of two channels to the groups of fascicles he observed in the common fibular nerve [9]. Multicontact nerve-cuff electrodes implanted in humans are available and provide balanced dorsiflexion in foot-drop applications [7,[11][12][13], supporting the observed common fibular fascicular anatomy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…O'Halloran et al made similar conclusions about generating pure dorsiflexion without inversion or eversion through balanced activation of two channels to the groups of fascicles he observed in the common fibular nerve [9]. Multicontact nerve-cuff electrodes implanted in humans are available and provide balanced dorsiflexion in foot-drop applications [7,[11][12][13], supporting the observed common fibular fascicular anatomy.…”
Section: Discussionmentioning
confidence: 51%
“…Implantable neural prostheses for foot drop generally use nerve-cuff electrodes to activate the motor nerves and lift the foot, and some record sensory information to trigger stimulation [1][2]4,[6][7][8][9][10][11][12][13]. However, most implantable neural prostheses provide only dorsiflexion to correct foot drop and do not provide active plantar flexion.…”
Section: Neural Prostheses For Ankle Controlmentioning
confidence: 99%
“…The prescription of an implantable peroneal nerve stimulator is only a treatment option when the main goal is to achieve an orthotic effect for the long term in drop foot patients [32]. Burridge et al [33] reported significant increases in mean gait distance and velocity (19%) using the ActiGait system. In a research conducted by Taylor et al [26] 46 drop foot patients were selected from ODFS system users that had skin irritation, difficulties with electrode placement or anticipated long-term use with the device.…”
Section: Implanted Fesmentioning
confidence: 99%
“…56 The other is a fourchannel device, developed at Aalborg University (Denmark) and utilizes a 4-channel nerve cuff electrode surgically placed around the common peroneal nerve. 57 Peroneal nerve stimulation (PNS) during gait has positive neuroprosthetic and therapeutic effects on ambulation. Neuroprosthetic effects have been shown in a number of case series studies and several RCTs, with outcome measures ranging from gait kinematic and spatiotemporal parameters to metabolic cost indices.…”
Section: Nmes Modalities For Lower Limb Rehabilitationmentioning
confidence: 99%